2018
DOI: 10.4049/jimmunol.1700417
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1/B7-H1 Inhibits Viral Clearance by Macrophages in HSV-1–Infected Corneas

Abstract: Immune privilege helps protect the cornea from damaging inflammation but can also impair pathogen clearance from this mucosal surface. Programmed death-ligand 1 (PD-L1 or B7-H1) contributes to corneal immune privilege by inhibiting the function of a variety of immune cells. We asked whether programmed death-1 (PD-1)/PD-L1 interaction regulates HSV-1 clearance from infected corneas. We show that PD-L1 is constitutively expressed in the corneal epithelium and is upregulated upon HSV-1 corneal infection, with pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…We also noticed that PD-L1 was up-regulated in the epithelium and stroma of untreated mice after HSV-1 infection in consistent with previous observations (Supplementary Fig. 9) 29 . Increased local PD-L1 expression may inhibit virus clearance by immune cells highlighting the importance of direct DNA degradation by CRISPR.…”
Section: Figuresupporting
confidence: 93%
“…We also noticed that PD-L1 was up-regulated in the epithelium and stroma of untreated mice after HSV-1 infection in consistent with previous observations (Supplementary Fig. 9) 29 . Increased local PD-L1 expression may inhibit virus clearance by immune cells highlighting the importance of direct DNA degradation by CRISPR.…”
Section: Figuresupporting
confidence: 93%
“…Previously, we have shown that ectopic expression of CD80 by HSV-1 increased CD80 binding to PD-L1 on DCs, allowing efficient infection and lysis of infected cells (19). Recently it was reported that PD-L1 Ϫ/Ϫ mice had lower virus replication in their eyes than WT mice, suggesting that PD-L1 expression on corneal cells negatively impacts the ability of the innate immune system to clear HSV-1 from infected corneas (59). This report is in line with our results of exacerbation of CS in HSV-CD80-infected mice due to the binding of HSV-CD80 to PD-L1 in the cornea (19).…”
Section: Discussionmentioning
confidence: 99%
“…3A). This could also be a result of sequestering PD-L1, because Jeon et al reported a negative effect of PD-L1 expression on viral clearance (62).…”
Section: Discussionmentioning
confidence: 99%